Faktor-Faktor yang Mempengaruhi Kejadian Plasenta Previa di Rumah Sakit Umum Daerah Kota Prabumulih - Dwi Saputri Mayang Sari; Yudi Budianto (Universitas Batanghari Jambi, 2021)
Placenta previa is a one of the risks in pregnancy. The research objectives are the factors that influence the incidence of placenta previa in the City Hospital of Prabumulih in 2019. The research method is analytic, using the Cross Sectional approach. The population of this research was all of the maternity mothers in the midwifery room of the Prabumulih City which were 1712 people. The research sample is part of the population of 324 people. The research instrument was a checklist. The results of the study based on univariate analysis revealed that from 324 respondents there were 53 respondents (16.4%) who had placenta previa and 271 respondents (83.6%) who did not have placenta previa, there were 22 respondents (6.8%) who were diagnosed with multiple pregnancy and 302 respondents (93.2%) who were not diagnosed with multiple pregnancy, there were 51 respondents (15.7%) who had a history of curettage and 273 people (84.3%) who had no history of curettage, there were 21 respondents ( 6.5%) who had a tumor and 303 people (93.5%) who did not have a tumor. From the bivariate analysis it is Conclusion there is a significant relationship between multiple pregnancy with the incidence of placenta previa with a P value of 0.000 <α 0.05, there is a significant relationship between the history of curettage with the incidence of placenta previa with a value of P value 0,000 <0.05 and there is a significant relationship between the tumor and the incidence placenta previa with a P value of 0,000 <0.05